2021
DOI: 10.1371/journal.ppat.1008748
|View full text |Cite
|
Sign up to set email alerts
|

Extensive proteomic and transcriptomic changes quench the TCR/CD3 activation signal of latently HIV-1 infected T cells

Abstract: The biomolecular mechanisms controlling latent HIV-1 infection, despite their importance for the development of a cure for HIV-1 infection, are only partially understood. For example, ex vivo studies have recently shown that T cell activation only triggered HIV-1 reactivation in a fraction of the latently infected CD4+ T cell reservoir, but the molecular biology of this phenomenon is unclear. We demonstrate that HIV-1 infection of primary T cells and T cell lines indeed generates a substantial amount of T cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…Host transcription factors, such NF-ĸB p65, Ap-1, Sp-1 and NFAT, with binding sites located within the viral Long Terminal Repeat (LTR), are required for HIV-1 gene expression and replication which can be regulated by activation/inhibition of TCR-related signaling pathways [9,10,17,19,21]. Knock-down of the expression of FADD [9] and inhibition of caspase-3 activities (Figure 1B) inactivates NF-ĸB p65, Ap-1, Sp-1 and NFAT through decreased/ inactivated signaling transduction of TCR-related pathways with down regulation of expression of TCRα/β, PKC, or PI3K/Akt [9] (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host transcription factors, such NF-ĸB p65, Ap-1, Sp-1 and NFAT, with binding sites located within the viral Long Terminal Repeat (LTR), are required for HIV-1 gene expression and replication which can be regulated by activation/inhibition of TCR-related signaling pathways [9,10,17,19,21]. Knock-down of the expression of FADD [9] and inhibition of caspase-3 activities (Figure 1B) inactivates NF-ĸB p65, Ap-1, Sp-1 and NFAT through decreased/ inactivated signaling transduction of TCR-related pathways with down regulation of expression of TCRα/β, PKC, or PI3K/Akt [9] (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Latent HIV proviruses are thought to be primarily reactivated in vivo through stimulation of the T-cell receptor (TCR). It has been reported that T cell activation is required forHIV-1 replication and gene expression, and T cells are generally activated through TCR, and CD3 [19,21], or/and PI3K/Akt [19]-related cell signaling pathways. These pathways can trigger and activate downstream molecules, such as Zap-70 and PLCγ1, and serially activate transcription factors, NF-ĸB p65, Ap-1, Sp-1 and NFAT.…”
Section: Caspase-3 Inhibitor Suppressed T-cell Receptor (Tcr)-related...mentioning
confidence: 99%
“…Moreover, given the increasingly well-established relationship between HIV infection and the persistent proinflammatory state, the search for drugs that cover the largest possible proportion of the viral reservoir have become a priority [ 75 ]. There is research into new molecular signaling pathways to improve the latency reversal process [ 76 , 77 , 78 ], although the complex signaling process regulating CD4+ T cell expression is not yet fully understood [ 79 ].…”
Section: Viral Latency and The Latent Cell Reservoirmentioning
confidence: 99%
“…8 The impact of latent reservoir cells on ART highlights the need for continuous research and the development of new therapies that can target and eliminate these reservoir cells. 9 In this work, we developed a nanoparticle formulation to improve ART for retroviral infections, with a focus on inactive HIV reservoir cells.…”
Section: Introductionmentioning
confidence: 99%
“…These reservoir cells comprise dormant viruses integrated to host genomes that cannot be eliminated by ART and can become active later, resulting in treatment failure and drug resistance . The impact of latent reservoir cells on ART highlights the need for continuous research and the development of new therapies that can target and eliminate these reservoir cells . In this work, we developed a nanoparticle formulation to improve ART for retroviral infections, with a focus on inactive HIV reservoir cells.…”
Section: Introductionmentioning
confidence: 99%